Interactive synchrony and infants’ vagal tone as an index of emotion regulation: associations within each mother- and father-infant dyad and across dyads - Puglisi, Nilo; Favez, Nicolas; Rattaz, Valentine; Epiney, Manuella; Razurel, Chantal; Tissot, Hervé (Frontiers in Psychology, 2023)
Introduction Studies have shown that infants’ emotion regulation capacities are closely linked to the quality of parent-infant interactions. However, these links have been mostly studied in mother-infant dyads and less is known about how the quality of father-infant interactions contributes to the development of emotion regulation during infancy. In this study, we aimed to investigate the links between interactive synchrony (i.e., an index of the quality of parent-infant coordination of interactive behaviors) and infants’ vagal tone (i.e., a physiological index of emotion regulation). To understand the respective contributions of both parents, as well as the interrelations between the functioning of both dyads within a family, we observed mothers and fathers from 84 families interacting with their infants. Methods Synchrony was assessed by using the CARE-Index; infants’ vagal tone was derived from the analysis of infants’ electrocardiograms recorded during the interactions. Moreover, to take the play’s order into account, we counterbalanced the procedure, so that approximately half of the mothers played first. We specified a first structural equation modeling (SEM) model to investigate the associations between interactive synchrony and the infants’ root mean square of successive differences (RMSSD), an index of vagal regulation, in the two successive parts of the play. We conducted a multigroup analysis in a second SEM model to investigate the associations of the first SEM model in two groups based on the order of interaction. Results The results of the SEM models showed that greater synchrony was related to greater infant RMSSD within mother-infant dyads and across one dyad to the other dyad in the full sample and in the group of fathers who interacted first with the infants. The associations between synchrony and infant vagal tone within father-infant dyads never appeared to be significant, nor did any associations within each dyad and across dyads when mothers interacted first. Discussion This study highlights that the links between interactions and infants’ vagal tone are sensitive to family members’ interdependencies and some conditions (the order of interaction).